Layoff Sentiment on Indonesian Twitter: Naïve Bayes Benchmarks and Human Resource Communication Strategy - Ikrima, Ihda Khairunisa; Mulyana, Amalia Rizky (Journal of Principles Management and Business, 2025)
In 2022, widespread workforce reductions in Indonesia precipitated extensive public discourse on social media platforms, particularly Twitter. While organizational downsizing is frequently adopted as a strategic response to economic uncertainty, empirical evidence suggests it may adversely affect corporate reputation and stakeholder trust, especially when communication is inadequate. This study examines public sentiment toward layoffs by analyzing tweets containing the Indonesian term “PHK” from November to December 2022. Employing automated sentiment classification and social network analysis, the research identifies sentiment distribution and thematic patterns in user-generated content. Findings reveal a sentiment distribution of 40% neutral, 37% negative, and 23% positive, with negative sentiment predominantly associated with job insecurity and neutral discourse reflecting informational reporting. These results align with existing literature on the reputational risks of downsizing. The study advocates for proactive stakeholder mapping, empathetic communication, and real-time sentiment monitoring. Timely dissemination of factual updates and responsive engagement may mitigate reputational damage and prevent sentiment drift. Strategic communication before, during, and after workforce restructuring is essential to preserve organizational legitimacy and minimize adverse market reactions.